Learn more about

Refine search

Results (displaying matches 1-50 of 1790) Next

Label Class Equation Sato-Tate \(\overline{\Q}\)-simple \(\GL_2\) Rank*
708.a.181248.1 708.a \(y^2 + (x^3 + 1)y = -x^6 - 4x^5 + 9x^4 + 48x^3 - 41x^2 - 98x - 36\) $\mathrm{USp}(4)$ 0
1170.a.10530.1 1170.a \(y^2 + (x^2 + x)y = 15x^6 + 28x^5 + 62x^4 + 59x^3 + 62x^2 + 28x + 15\) $G_{3,3}$ 0
1935.a.52245.2 1935.a \(y^2 + xy = x^5 - 2x^4 - 82x^3 - 20x^2 + 927x - 1134\) $\mathrm{USp}(4)$ 0
1950.a.105300.1 1950.a \(y^2 + (x^2 + x)y = x^5 + 36x^4 + 330x^3 + 36x^2 + x\) $G_{3,3}$ 0
2058.a.2058.1 2058.a \(y^2 + (x^3 + 1)y = 5x^6 - 4x^5 - 5x^4 + 14x^3 - 5x^2 - 4x + 5\) $N(G_{1,3})$ 0
2610.a.2610.1 2610.a \(y^2 + (x^3 + 1)y = 8x^6 + 19x^5 + 39x^4 + 41x^3 + 39x^2 + 19x + 8\) $G_{3,3}$ 0
2730.b.38220.1 2730.b \(y^2 + (x^2 + x)y = x^5 + 28x^4 + 201x^3 + 28x^2 + x\) $G_{3,3}$ 0
2739.a.2739.1 2739.a \(y^2 + (x^2 + x + 1)y = 3x^6 + 26x^5 + 40x^4 + 25x^3 + 22x^2 + 7x - 8\) $\mathrm{USp}(4)$ 0
2880.c.368640.1 2880.c \(y^2 = 6x^6 - 13x^5 + 27x^4 - 28x^3 + 27x^2 - 13x + 6\) $G_{3,3}$ 0
2898.a.8694.1 2898.a \(y^2 + (x^3 + 1)y = -10x^6 + 18x^5 - 23x^4 + 36x^3 - 23x^2 + 18x - 10\) $G_{3,3}$ 0
2976.a.761856.1 2976.a \(y^2 + y = -4x^6 - 20x^5 - 19x^4 + 18x^3 + 5x^2 - 3x - 1\) $\mathrm{USp}(4)$ 0
3528.d.98784.1 3528.d \(y^2 + (x^3 + x)y = 5x^6 + 35x^4 + 58x^2 - 6\) $G_{3,3}$ 0
3680.b.942080.1 3680.b \(y^2 = x^5 - 56x^3 - 245x^2 - 383x - 217\) $\mathrm{USp}(4)$ 0
3792.b.485376.1 3792.b \(y^2 + (x + 1)y = 56x^6 + 8x^5 - 67x^4 - 7x^3 + 27x^2 + x - 4\) $\mathrm{USp}(4)$ 0
4489.c.4489.1 4489.c \(y^2 + (x^3 + x^2 + 1)y = -x^6 + 7x^4 - 2x^3 - 21x^2 + x + 18\) $G_{3,3}$ 0
4667.a.4667.1 4667.a \(y^2 + (x^2 + x)y = 14x^6 + 29x^5 + 68x^4 + 71x^3 + 79x^2 + 39x + 22\) $\mathrm{USp}(4)$ 0
4925.a.4925.1 4925.a \(y^2 + y = 5x^6 - 5x^5 + 12x^3 + 2x^2 - 5x - 2\) $\mathrm{USp}(4)$ 0
5077.a.5077.1 5077.a \(y^2 + xy = x^5 + 7x^4 + 8x^3 - 16x^2 + x\) $\mathrm{USp}(4)$ 0
5170.a.10340.1 5170.a \(y^2 + (x^3 + 1)y = -3x^6 + 25x^4 + 14x^3 - 46x^2 - 22x + 24\) $\mathrm{USp}(4)$ 0
5280.d.84480.1 5280.d \(y^2 + xy = 24x^6 + 95x^4 + 125x^2 + 55\) $G_{3,3}$ 0
5329.a.5329.1 5329.a \(y^2 + (x^3 + x + 1)y = -x^6 - 8x^5 - 16x^4 + 25x^3 - 40x^2 + 31x - 8\) $G_{3,3}$ 0
5835.a.5835.1 5835.a \(y^2 + (x^3 + x)y = x^6 - x^5 + 8x^4 + 3x^3 + 11x^2 + 21x + 8\) $\mathrm{USp}(4)$ 0
6369.a.19107.1 6369.a \(y^2 + (x + 1)y = 18x^6 - 3x^5 + 4x^4 + 14x^3 - 4x^2 + 3x + 1\) $\mathrm{USp}(4)$ 0
6570.a.479610.1 6570.a \(y^2 + (x^3 + 1)y = x^6 + x^5 - 5x^4 + 2x^3 - x^2 - 3x - 1\) $\mathrm{USp}(4)$ 0
6880.a.110080.1 6880.a \(y^2 + y = -8x^6 - 16x^5 + 3x^4 + 19x^3 + 7x^2 - x - 1\) $\mathrm{USp}(4)$ 0
7440.e.476160.1 7440.e \(y^2 + (x^3 + x)y = -x^6 + 6x^4 + 13x^2 - 155\) $G_{3,3}$ 0
7920.a.7920.1 7920.a \(y^2 + (x^2 + 1)y = 15x^6 + 37x^4 + 30x^2 + 8\) $G_{3,3}$ 0
8172.a.523008.1 8172.a \(y^2 + x^2y = x^5 + x^4 - 61x^3 - 98x^2 + 940x + 1848\) $\mathrm{USp}(4)$ 0
8400.a.8400.1 8400.a \(y^2 + (x^3 + x)y = x^6 + 16x^4 + 72x^2 + 105\) $G_{3,3}$ 0
8470.a.42350.1 8470.a \(y^2 + (x^2 + x)y = -3x^6 + 4x^5 + 11x^3 + 4x - 3\) $G_{3,3}$ 0
8640.a.17280.1 8640.a \(y^2 + (x^3 + x)y = 3x^4 + 8x^2 - 30\) $G_{3,3}$ 0
8670.b.312120.1 8670.b \(y^2 + (x^2 + x)y = 5x^6 + 15x^5 + 34x^4 + 43x^3 + 42x^2 + 23x + 8\) $G_{3,3}$ 0
8730.a.235710.1 8730.a \(y^2 + (x^2 + x)y = x^5 + 44x^4 + 491x^3 + 44x^2 + x\) $G_{3,3}$ 0
8960.c.17920.1 8960.c \(y^2 + y = -4x^6 - 10x^5 + 3x^4 + 15x^3 - x^2 - 4x - 1\) $\mathrm{USp}(4)$ 0
9163.a.155771.1 9163.a \(y^2 + (x^2 + 1)y = x^5 - 37x^4 + 41x^3 - 3x^2 - 5x - 1\) $\mathrm{USp}(4)$ 0
9318.a.9318.1 9318.a \(y^2 + xy = x^5 + x^4 - 13x^3 - 58x^2 - 69x - 25\) $\mathrm{USp}(4)$ 0
9504.e.304128.1 9504.e \(y^2 + (x^3 + x)y = 8x^4 + 80x^2 + 132\) $G_{3,3}$ 0
9828.a.39312.1 9828.a \(y^2 + (x^2 + 1)y = -7x^6 - 39x^4 + 40x^2 - 10\) $G_{3,3}$ 0
10075.c.654875.1 10075.c \(y^2 + xy = 5x^5 + 41x^4 + 88x^3 + 16x^2 + x\) $\mathrm{USp}(4)$ 0
10080.a.60480.1 10080.a \(y^2 + xy = -15x^6 + 58x^4 - 60x^2 + 7\) $G_{3,3}$ 0
10080.b.60480.1 10080.b \(y^2 + xy = -15x^6 - 58x^4 - 60x^2 - 7\) $G_{3,3}$ 0
10080.c.141120.1 10080.c \(y^2 + (x^3 + x)y = -x^6 + 35x^4 - 560x^2 + 2940\) $G_{3,3}$ 0
10086.b.413526.1 10086.b \(y^2 + (x^3 + x)y = -x^6 - 4x^5 - 7x^4 - 6x^3 + 3x + 3\) $\mathrm{USp}(4)$ 0
10288.a.10288.1 10288.a \(y^2 + (x + 1)y = -x^6 - 4x^5 + 2x^4 + 12x^3 - 9x^2 - 1\) $\mathrm{USp}(4)$ 0
10710.a.32130.1 10710.a \(y^2 + (x^2 + x)y = -x^6 + 24x^4 + x^3 - 192x^2 - 12x + 494\) $G_{3,3}$ 0
10752.b.10752.1 10752.b \(y^2 + xy = 6x^6 + 20x^4 + 21x^2 + 7\) $G_{3,3}$ 0
11088.c.99792.1 11088.c \(y^2 + (x^3 + x)y = 5x^6 + 60x^4 + 232x^2 + 297\) $G_{3,3}$ 0
11320.a.45280.1 11320.a \(y^2 + (x + 1)y = -52x^6 - 34x^5 + 8x^4 + 6x^3 + 3x^2 - 1\) $\mathrm{USp}(4)$ 0
11413.a.11413.1 11413.a \(y^2 + (x^3 + x + 1)y = x^6 + 2x^5 + 4x^4 + 3x^3 + 4x^2 + x + 1\) $\mathrm{USp}(4)$ 0
11488.c.183808.1 11488.c \(y^2 + xy = 8x^6 - 20x^5 + 33x^4 - 32x^3 + 23x^2 - 10x + 3\) $\mathrm{USp}(4)$ 0
Next

Download all search results for